Performance regulation in a networked healthcare system: From cosmetic to institutionalized compliance. (6th June 2018) - van Erp, Judith; Wallenburg, Iris; Bal, Roland
Abstract : This article studies the role of a public regulator in managing the performance of healthcare professionals. It combines a networked governance perspective with responsive regulation theory to show the mechanisms that have added to significant changes in medical cost management in the Netherlands. In a five‐year period, hospital practices transitioned from cosmetic compliance with performance regulation and strategic upcoding to institutionalized compliance more in line with regulatory goals. The article demonstrates how policy changes transformed incentive structures, introduced new forms of accountability, and added actors to the network with technocratic disciplining tasks. The networked character of performance regulation offered opportunities for a responsive, non‐coercive regulatory strategy that engaged various actors in a regulatory conversation about strategic coding. Responsive regulation can reduce strategic responses to performance regulation and manage the gap between administrative and clinical logics. The case study contributes to our understanding of the effectiveness of responsive, non‐punitive regulation in networked settings.